2018
DOI: 10.3389/fpsyg.2018.00854
|View full text |Cite
|
Sign up to set email alerts
|

Combined Cognitive-Motor Rehabilitation in Virtual Reality Improves Motor Outcomes in Chronic Stroke – A Pilot Study

Abstract: Stroke is one of the most common causes of acquired disability, leaving numerous adults with cognitive and motor impairments, and affecting patients’ capability to live independently. Virtual Reality (VR) based methods for stroke rehabilitation have mainly focused on motor rehabilitation but there is increasing interest toward the integration of cognitive training for providing more effective solutions. Here we investigate the feasibility for stroke recovery of a virtual cognitive-motor task, the Reh@Task, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 45 publications
1
79
0
Order By: Relevance
“…In this randomized controlled pilot trial, we tested a novel rehabilitation program in VR that trains several cognitive domains in conjunction. Together with a few other clinical trials [38,65], we are among the first in addressing the multidimensionality of cognitive impairment after stroke, by providing a VR-based cognitive training that adapts its difficulty optimally to the ability of the patient while providing an embodied training with rewarding feedback [81]. Our data set reveals interesting insights when a heterogeneous sample without a specific cognitive deficit is selected.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this randomized controlled pilot trial, we tested a novel rehabilitation program in VR that trains several cognitive domains in conjunction. Together with a few other clinical trials [38,65], we are among the first in addressing the multidimensionality of cognitive impairment after stroke, by providing a VR-based cognitive training that adapts its difficulty optimally to the ability of the patient while providing an embodied training with rewarding feedback [81]. Our data set reveals interesting insights when a heterogeneous sample without a specific cognitive deficit is selected.…”
Section: Discussionmentioning
confidence: 96%
“…As there is no existing study from which estimations for our primary outcome measurements could have been obtained, the sample size had to be predicted instead of calculated through a power analysis. Based on our previous experiments that proved to be achievable with the resources and time available [32,64], other trials with similar interventions [38,65] and the doctor's estimation of recruitment pace, a sample size of 30 participants was deemed adequate. The trial concluded when the sample size for a complete case analysis was reached.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…12 Standard rehabilitation protocols are considered as less intensive given their repetitive nature, poor cognitive stimuli, and lack of direct feedback stimuli. 14 In this scenario, the use of VR is a relatively novel adjunct, which can compensate for the lack of intensive treatments. Recent reviews and meta-analysis summarize the recent results of the use of VR as a facilitator on motor rehabilitation programs, with positive results.…”
Section: Background and Rationalementioning
confidence: 99%
“…Particularly, the patient was able to reach the highest score of the proximal arm (34/34) and wrist/hand (23/24). Compared to the other methods, Faria et al reported that both VR and control group showed significant improvements at the end of treatment in wrist/hand Fugl-Meyer (p = 0.034 and p = 0.04) [39]. However, these improvements were significant with respect to baseline, but they were modest for both groups at end of treatment (0.8 ± 1.4 in VR versus 1.3 ± 2.3 in control).…”
Section: Discussionmentioning
confidence: 99%